153k views
5 votes
PLEASE HELP 100 POINTS!!!

Complete the proof.

If 6+5x+3=−4x , then x=−1 .

Drag and drop the reasons to correctly complete each box.

PLEASE HELP 100 POINTS!!! Complete the proof. If 6+5x+3=−4x , then x=−1 . Drag and-example-1
User Aviran
by
6.1k points

2 Answers

0 votes

here is your answer.

4x − 1 = −2 (x + 1) ⇒ Given

have a good day.

User Cbowns
by
5.5k points
2 votes

Answer: AND Step-by-step explanation:

4x − 1 = −2 (x + 1) ⇒ Given

4x−1=−2x−2⇒ Distributive property (since we've multiplied out -2(x+1))

6x−1=−2 ⇒ Addition or Subtraction Property of Equality (We've added 2x onto the 4x to get 6x)

6x=−1 ⇒ Commutative Property (We've moved -1 to the other side to get the sum -2+1 = -1)

x=−¹/₆ ⇒ Multiplication or Division Property of Equality (We divided both sides by 6)

User Elevener
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.